2010
DOI: 10.1371/journal.ppat.1000815
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Effector- and Central-Memory Responses to Toxoplasma gondii Infection by IL-12 Revealed by Tracking of Tgd057-Specific CD8+ T Cells

Abstract: Production of the pro-inflammatory cytokine IL-12 by innate phagocytes drives the differentiation of IFN-γ-producing effector T cells during Toxoplasma gondii infection. However, the role of IL-12 in the regulation of memory CD8+ T cell differentiation and function during murine toxoplasmosis is unclear. To track memory CTL development, we identified a novel H-2Kb-restricted CTL population specific for the Toxoplasma antigen tgd057. Tgd057-specific CTLs were induced by both vaccination and natural peroral infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
94
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 54 publications
(80 reference statements)
6
94
0
1
Order By: Relevance
“…Secretion of parasite antigens into the host cell is known to be important for presentation via the MHC class I pathway, which samples the host cytosol and stimulates CD8 T cell responses to intracellular pathogens. This is in line with evidence that secretion into the host cell promotes recognition by CD8 T cells (31) and the fact that all of the T. gondii CD8 epitopes identified to date are derived from secreted parasite proteins (4,16,40,62). On the other hand, the impact of secretion on MHC class II presentation of potential parasite antigens is less clear, since both secreted and nonsecreted parasite antigens should have ready access to the class II MHC pathway via phagocytosis of intact parasites and debris.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Secretion of parasite antigens into the host cell is known to be important for presentation via the MHC class I pathway, which samples the host cytosol and stimulates CD8 T cell responses to intracellular pathogens. This is in line with evidence that secretion into the host cell promotes recognition by CD8 T cells (31) and the fact that all of the T. gondii CD8 epitopes identified to date are derived from secreted parasite proteins (4,16,40,62). On the other hand, the impact of secretion on MHC class II presentation of potential parasite antigens is less clear, since both secreted and nonsecreted parasite antigens should have ready access to the class II MHC pathway via phagocytosis of intact parasites and debris.…”
Section: Discussionsupporting
confidence: 69%
“…This approach has been used to examine CD8 T cell responses to T. gondii, leading to the identification of a number of endogenous CD8 antigens (4,7,16,40,62). Most strikingly, mice possessing the MHC-I molecule L d mount an immunodominant response to the HF10 decapeptide derived from the T. gondii protein GRA6 (4).…”
mentioning
confidence: 99%
“…Hence parasitespecific CD8 T cells are primed in a low-Ag, IL-12-poor environment. This could explain why only a small percentage of effector CD8 T cells expresses KLRG1 and 70-80% of the CD8 surviving contraction are T CM -like cells (31).…”
Section: Discussionmentioning
confidence: 99%
“…2B). A recent study demonstrated that the generation of KLRG1 + effector CD8 T cells is governed by IL-12 (31). Thus, we assessed the IL-12 p35 and IL-12/IL-23 p40 mRNA expression by splenic CD11c hi DCs at days 1, 3, and 6 after L. donovani infection.…”
Section: B Cells Suppress the Generation Of Effector Memory T Cells Imentioning
confidence: 99%
“…Finally, our observations may have important implications regarding the basis for the strong immunodominance pattern observed after experimental infection with other intracellular parasites such as Plasmodium, Toxoplasma gondii and Theileria parva [50,51,[54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%